Analysis of Classroom Management in Learning Quality, Affective Support and Cognitive Activation at Junior High School - Mohammad Mustari; Ilham Muhammad (STAI Hubbulwathan Duri, 2023)
The objective of this study is to analyze how classroom management and learning process is carried out to achieve the quality of learning and have cognitive abilities, attitudes, character, behavior, emotions, interests, and values of individuals in realizing the goals of National Education by doing concrete movements in improving the quality of education through the quality of learning. This study used qualitative methods by collecting data through several sources such as basic data on education (Dapodik), with techniques for collecting and testing the credibility of data and documentation. The research sample was the 2021 education report card which shows the low quality of learning. The research was conducted using interview and document analysis techniques. The results found that there is a need for training in classroom management for junior high school-level teachers. In light of the results, the Education Authorities of Mataram City need to increase teacher competency in classroom management and other support according to the indicators in the education report card. It is suggested that Education Authorities make policies related to learning quality improvement by providing training or workshops for teachers.